Caiçara Fandango: a reading from folk communication and the map of mediations: uma leitura a partir da folkcomunicação e do mapa das mediações (Revista Internacional de Folkcomunicação, 2024)
The Fandango Caiçara is a musical artistic expression found on the southern coast of the state of São Paulo and Paraná. It is part of the social way of life of coastal rural communities, and its songs and dances are linked to work, entertainment, and religious festivals. Understanding the Fandango Caiçara through the lens of Folkcommunication, this article aims to reflect on the relationships within the communicational chain of this sociocultural practice, based on the map of mediations presented by Jesús Martín Barbero. As a methodology, it employs bibliographic research and analytical approaches to broaden perspectives on each element of the communicational chain. The results provide an adaptation of the map of mediations applied to the Fandango, thus offering possible analytical perspectives on popular cultural productions.